2005
DOI: 10.1002/biof.5520230305
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine improves dysfunction of peroxisome proliferator-activated receptor α and microsomal triglyceride transfer protein on abnormalities in lipid metabolism in ethanol-fed rats

Abstract: We report the effects of Traditional Chinese Medicine (TCM) on alcohol-induced fatty liver in rats. TCM consists of Astragalus membranaceus, Morus alba, Crataegus pinnatifida, Alisma oriental, Salvia miltiorrhiza and Pueraria lobata. The rats were separated randomly into five groups; the CD group (n=10), which was fed a control diet for 10 weeks, the ED group (n=10), which was fed an isocaloric liquid diet containing ethanol for 10 weeks and given daily oral doses of TCM (0.222 g/kg/day; TCM222, 0.667 g/kg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…There is no evidence showing that ShanZha could induce an activation of PPAR␣. Our result regarding ShanZha increased the activity of PPAR␣ is consistent with a previous report that Crataegus pinnatifida, containing in a traditional Chinese medicine mix formula, diminished the accumulation of lipids in liver through regulating PPAR␣ activity (Kwon et al, 2005). It can be considered that ShanZha acts as an activator of PPAR␣ to modulate the function of adipose tissue.…”
Section: Discussionsupporting
confidence: 93%
“…There is no evidence showing that ShanZha could induce an activation of PPAR␣. Our result regarding ShanZha increased the activity of PPAR␣ is consistent with a previous report that Crataegus pinnatifida, containing in a traditional Chinese medicine mix formula, diminished the accumulation of lipids in liver through regulating PPAR␣ activity (Kwon et al, 2005). It can be considered that ShanZha acts as an activator of PPAR␣ to modulate the function of adipose tissue.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, some reports showed that Lotus leaf leads to a decrease in the levels of serum lipid (Cho et al, 2007;Kim et al, 2013). Furthermore, many studies uncovered that TCM could affect total lipid metabolism by reducing serum lipid level (Guo et al, 2015;Kwon et al, 2005;Tu et al, 2003). The present study showed a significant decrease in hepatic fat percentage and a decrease trending in abdominal fat percentage after the dietary supplemented with TCM.…”
Section: Discussionsupporting
confidence: 63%
“…Body weight loss is a distinctive feature of CCl 4 -induced hepatotoxicity [44]. One of the largest organ is liver that CCl 4 administrated caused a rapid accumulation of triglycerides in the liver due to a block secretion of very low density lipoprotein by hepatocytes [45, 46]. Furthermore, increase in the total body weight was detected after administration of olive oil and N. Sativa oil to rats received CCl 4 .…”
Section: Discussionmentioning
confidence: 99%